The landscape of Mucopolysaccharidosis in Southern and Eastern European countries: a survey from 19 specialistic centers - Tylki-Szymańska, Anna; Almássy, Zsuzsanna; Christophidou-Anastasiadou, Violetta; Avdjieva-Tzavella, Daniela; Barisic, Ingeborg; Cerkauskiene, Rimante; Cuturilo, Goran; Djiordjevic, Maja; Gucev, Zoran; Hlavata, Anna; Kieć-Wilk, Beata; Magner, Martin; et al. (Orphanet journal of rare diseases, 2022)
BACKGROUND: Mucopolysaccharidoses (MPS) are a group of lysosomal storage disorders caused by defects in genes coding for different lysosomal enzymes which degrade glycosaminoglycans. Impaired lysosomal degradation causes cell dysfunction leading to progressive multiorgan involvement, disabling consequences and poor life expectancy. Enzyme replacement therapy (ERT) is now available for most MPS types, offering beneficial effects on disease progression and improving quality of life of patients. The landscape of MPS in Europe is not completely described and studies on availability of treatment show that ERT is not adequately implemented, particularly in Southern and Eastern Europe. In this study we performed a survey analysis in main specialist centers in Southern and Eastern European countries, to outline the picture of disease management in the region and understand ERT implementation. Since the considerable number of MPS IVA patients in the region, particularly adults, the study mainly focused on MPS IVA management and treatment. RESULTS: 19 experts from 14 Southern and Eastern European countries in total responded to the survey. Results outlined a picture of MPS management in the region, with a high number of MPS patients managed in the centers and a high level of care. MPS II was the most prevalent followed by MPS IVA, with a particular high number of adult patients. The study particularly focused on management and treatment of MPS IVA patients. Adherence to current European Guidelines for follow-up of MPS IVA patients is generally adequate, although some important assessments are reported as difficult due to the lack of MPS skilled specialists. Availability of ERT in Southern and Eastern European countries is generally in line with other European regions, even though regulatory, organizational and reimbursement constrains are demanding. CONCLUSIONS: The landscape of MPS in Southern and Eastern European countries is generally comparable to that of other European regions, regarding epidemiology, treatment accessibility and follow up difficulties. However, issues limiting ERT availability and reimbursement should be simplified, to start treatment as early as possible and make it available for more patients. Besides, educational programs dedicated to specialists should be implemented, particularly for pediatricians, clinical geneticists, surgeons, anesthesiologists and neurologists.
Keywords: mukopolysacharidóza IV; mukopolysacharidóza II; mukopolysacharidózy; Treatment accessibility; Enzyme replacement therapy; dospělí; Humans; Mucopolysaccharidosis II; Adult; Quality of Life; enzymová substituční terapie; Southern and Eastern European countries; Enzyme Replacement Therapy; kvalita života; Mucopolysaccharidoses; lidé; Mucopolysaccharidosis IV; Morquio A syndrome